Golgi α-mannosidase II deficiency in vertebrate systems: implications for asparagine-linked oligosaccharide processing in mammals - Moremen, Kelley W (BBA - General Subjects, 2002)
The maturation of N-glycans to complex type structures on cellular and secreted proteins is essential for the roles that these structures play in cell adhesion and recognition events in metazoan organisms. Critical steps in the biosynthetic pathway leading from high mannose to complex structures include the trimming of mannose residues by processing mannosidases in the endoplasmic reticulum (ER) and Golgi complex. These exo-mannosidases comprise two separate families of enzymes that are distinguished by enzymatic characteristics and sequence similarity. Members of the Class 2 mannosidase family (glycosylhydrolase family 38) include enzymes involved in trimming reactions in N-glycan maturation in the Golgi complex (Golgi mannosidase II) as well as catabolic enzymes in lysosomes and cytosol. Studies on the biological roles of complex type N-glycans have employed a variety of strategies including the treatment of cells with glycosidase inhibitors, characterization of human patients with enzymatic defects in processing enzymes, and generation of mouse models for the enzyme deficiency by selective gene disruption approaches. Corresponding studies on Golgi mannosidase II have employed swainsonine, an alkaloid natural plant product that causes “locoism”, a phenocopy of the lysosomal storage disease, α-mannosidosis, as a result of the additional targeting of the broad-specificity lysosomal mannosidase by this compound. The human deficiency in Golgi mannosidase II is characterized by congenital dyserythropoietic anemia with splenomegaly and various additional abnormalities and complications. Mouse models for Golgi mannosidase II deficiency recapitulate many of the pathological features of the human disease and confirm that the unexpectedly mild effects of the enzyme deficiency result from a tissue-specific and glycoprotein substrate-specific alternate pathway for synthesis of complex N-glycans. In addition, the mutant mice develop symptoms of a systemic autoimmune disorder as a consequence of the altered glycosylation. This review will discuss the biochemical features of Golgi mannosidase II and the consequences of its deficiency in mammalian systems as a model for the effects of alterations in vertebrate N-glycan maturation during development.